Retrotransposon Ty1 integration targets specifically positioned asymmetric nucleosomal DNA segments in tRNA hotspots - Mularoni, Loris; Zhou, Yulian; Bowen, Tyson; Gangadharan, Sunil; Wheelan, Sarah J.; Boeke, Jef D. (Genome Research, 2012)
The Saccharomyces cerevisiae genome contains about 35 copies of dispersed retrotransposons called Ty1 elements. Ty1 elements target regions upstream of tRNA genes and other Pol III-transcribed genes when retrotransposing to new sites. We used deep sequencing of Ty1-flanking sequence amplicons to characterize Ty1 integration. Surprisingly, some insertions were found in mitochondrial DNA sequences, presumably reflecting insertion into mitochondrial DNA segments that had migrated to the nucleus. The overwhelming majority of insertions were associated with the 5′ regions of Pol III transcribed genes; alignment of Ty1 insertion sites revealed a strong sequence motif centered on but extending beyond the target site duplication. A strong sequence-independent preference for nucleosomal integration sites was observed, in distinction to the preferences of the Hermes DNA transposon engineered to jump in yeast and the Tf1 retrotransposon of Schizosaccharomyces pombe, both of which prefer nucleosome free regions. Remarkably, an exquisitely specific relationship between Ty1 integration and nucleosomal position was revealed by alignment of hotspot Ty1 insertion position regions to peak nucleosome positions, geographically implicating nucleosomal DNA segments at specific positions on the nucleosome lateral surface as targets, near the “bottom” of the nucleosome. The specificity is observed in the three tRNA 5′-proximal nucleosomes, with insertion frequency dropping off sharply 5′ of the tRNA gene. The sites are disposed asymmetrically on the nucleosome relative to its dyad axis, ruling out several simple molecular models for Ty1 targeting, and instead suggesting association with a dynamic or directional process such as nucleosome remodeling associated with these regions.
10.1101/gr.129460.111